Work Ethic of Women Laweyan Batik Craftsmen During the Covid-19 Pandemic - Bawono, Bachtiar Suryo; Sakuntalawati, LV Ratna Devi; Wijaya, Mahendra; Zuber, Ahmad; Kartono, Drajat Tri (Eastasouth Institute, 2024)
At the beginning of 2020, the global COVID-19 pandemic crisis occurred which had an impact on the batik industry in Laweyan Village, namely a decline in sales of up to 60% and the threat of bankruptcy. The formulation of the research problem is what is the work ethic of women Laweyan batik craftsmen during the COVID-19 pandemic. This research uses a qualitative method with a case study approach. There are two sampling techniques used in this research, namely snowball sampling which is used to look for informants for women craftsmen through key informants from the management of the Laweyan Batik Village Development Forum (FPKBL), and purposive sampling is used to find out whether the informant knows the data being sought. The research results found that women Batik Laweyan craftsmen had a work ethic during the COVID-19 pandemic. Data was obtained through 10 dimensions of work ethic theory, which shows that female Laweyan batik craftsmen still had a work ethic when the COVID-19 pandemic occurred. This research concludes that Laweyan Batik craftsmen still have a work ethic even though they are experiencing the COVID-19 pandemic crisis.